A Study on Regional Specialization of China’s Agricultural Production: Recent Trends and Drivers - Ma, Meilin; Steinbach, Sandro; Wu, Junqian (Asian Journal of Agriculture and Rural Development, 2014)
The paper examines trends and drivers for regional specialization of China’s agricultural produc-tion for 2003-2011. We apply the Regional Specialization Index to a data set of commodities that covers 70 percent of China’s crop and livestock production. Actual prices at the provincial level are used and a seven-region framework is established that accurately reflects China’s agro-ecological characteristics. Our findings show that inequality of specialization among the Chinese regions has narrowed, with the year 2007 as a turning point. We argue that the enhanced regional specialization is due to less government intervention and more openness to international markets. Growing economic freedom, accompanied by intensified internal and external competition, has driven the regions to adjust agricultural production structures closely according to comparative advantages. Recent trends of specialization are identified and explained. Moreover, quantitative evidence to relevant agricultural policies is provided.